2020
DOI: 10.1002/anie.202012216
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3‐hexylthiophene)s Functionalized with N‐Heterocyclic Carbenes as Robust and Conductive Ligands for the Stabilization of Gold Nanoparticles

Abstract: Recently, N‐heterocyclic carbenes (NHCs) are explored as anchor groups to bind organic ligands to colloidal gold (i.e. gold nanoparticles, Au NPs), yet these efforts are confined to non‐conjugated ligands so far—that is, focused solely on exploiting the stability aspect. Using NHCs to link Au NPs and electronically active organic components, for example, conjugated polymers (CPs), will allow capitalizing on both the stability as well as the inherent conductivity of the NHC anchors. Here, we report three types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Lissel and Fery also found that increasing the denticity of their poly(3-hexylthiophene)-NHCs resulted in NHC-AuNPs with increased thermal stability when heated for 24 hours at 100 1C. 96 As expected, multidentate NHC systems provide greater thermal stability to AuNPs against particle ripening.…”
Section: Nhcs On Gold Nanoparticlesmentioning
confidence: 74%
“…Lissel and Fery also found that increasing the denticity of their poly(3-hexylthiophene)-NHCs resulted in NHC-AuNPs with increased thermal stability when heated for 24 hours at 100 1C. 96 As expected, multidentate NHC systems provide greater thermal stability to AuNPs against particle ripening.…”
Section: Nhcs On Gold Nanoparticlesmentioning
confidence: 74%
“…Au NP stability should always be clearly assessed by a useful analytical tool, that is, surface plasmon resonance (SPR); for example, UV peak broadening is ascribed to differently sized nanoparticles present in solution . Moreover, a redshift or peak loss is demonstrative of their aggregations . In general, Au nanoparticles at about 520 nm are known with a strong surface plasmon absorbance, which is dependent on the NPs’ material properties, size, shape, surrounding media, and other surrounding nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…[ 70 ] Further, in heterogeneous colloidal engineering, [ 71 ] conductive ligands can also be used as an anchor group to attach organic ligands. [ 72 ] With a view toward the applicability of the method, we have shown a clear correlation between excitation of WPP in pure gold nanosphere grating supported on TiO 2 waveguide, and the decomposition of MO dye as a consequence of hot‐electron transfer from 1D colloidal Au grating into TiO 2 under visible light illumination. We envisage that the method is a stepping stone for the printing of various colloidal geometries and holds potential in applications in colloidal nanobiophotonics, nanochemistry, and nanosensing.…”
Section: Discussionmentioning
confidence: 99%